DIGITAL INFLUENCERS, MONETIZATION MODELS AND PLATFORMS AS TRANSACTIONAL SPACES - Goanta, Catalina; Bertaglia, Thales Costa (Brazilian Creative Industries Journal, 2023)
This paper aims to discuss the impact of digital influencers’ content monetization on social media in the context of platform governance. For achieving this objective, it characterizes the Monetization Supply Chain and the different monetization models as ad revenue, on-platform influencer marketing; subscription, tokenization, crowdfunding; direct selling; creator funds; besides the traditional influencer marketing. It also presents preliminary analyses of a dataset of posts by 400 influencers from four countries: Brazil, Germany, the Netherlands and the United States of America to understand how content creators from different countries are framing sponsored content.